The models of behaviour ofthe old generation historians in the presence of sovietization process - Aurimas Švedas (Lietuvos Istorijos Studijos)
Ever since Lithuania has restored its independence in 1990, wide-ranging debates have been taking place on a question of individual and societal conformance, resistance, and collaboration during the times of Soviet occupation. This article inquires into strategies and tactics of behavior that the most famous historians of independent Lithuania have chosen to pursue in the presence of existential and professional challenges made by the Soviet occupation and its totalitarian system.